Factors predicting malignancy in patients with polymyositis and dermatomyostis: a systematic review and meta-analysis. - Xin Lu; Hanbo Yang; Xiaoming Shu; Fang Chen; Yinli Zhang; Sigong Zhang; Qinglin Peng; Xiaolan Tian; Guochun Wang (PLoS ONE)
Objective To define potential factors that could predict concomitant neoplastic diseases in patients diagnosed with PM/DM, which could inform screening decisions. Methods Two researchers independently reviewed articles from Pubmed (MEDLINE), EMBASE, Cochrane Plus Library and ISI Web of Knowledge with no restrictions on study design or language. Given that some of the studies combined PM and DM patients as research subjects while others included only DM patients, data were subjected to meta-analyses for all combined PM/DM studies and studies that included only DM patients to obtain informative results. Results For PM/DM patients, the following factors are all associated with an increased risk of malignancy: older age, age greater than 45, male sex, dysphagia, cutaneous necrosis, cutaneous vasculitis, rapid onset of myostis (<4 weeks), elevated CK, higher ESR, higher CRP levels. Several factors were associated with lower-than-average risk, including the presence of ILD, arthritis/arthralgia, Raynaud's syndrome, or anti-Jo-1 antibody. For DM patients, results indicated an increased risk of malignancy with older age, male sex, the presence of cutaneous necrosis, elevated ESR (>35 mm/hr), higher CRP levels, or anti-p155 antibody. In addition, the presence of anti-ENA antibodies seem to be related to reduced risk of malignancy. Conclusion Awareness and implementation of early-stage cancer screening in PM/DM patients who have these identified factors--such as being older than 45, male sex, cutaneous necrosis, cutaneous vasculitis--are of crucial importance from public health and clinical perspectives and provide insight into the etiopathogenesis of CAM.